Robot-based Incremental Forming: Springback Effect Compensation Model for Various Materials - Shaker, Walid K.; Klimchik, Alexandr (International Conference on Control, Decision and Information Technologies (Online), 2024)
The springback effect refers to the tendency of a material to partially return to its original shape after deformation, especially in incremental metal forming processes. It poses a significant challenge in achieving precise and accurate final shapes, often requiring compensation strategies to reduce its impact. This study focuses on the evaluation and development related to a springback compensation model for incremental sheet metal forming processes. The proposed model aims to optimize toolpaths to counteract springback by addressing deviations between the formed and intended shapes. Performance assessment involved offline numerical simulations using Abaqus/CAE software across various materials. Results demonstrate significant efficacy, with mean error reductions exceeding 60% across different materials. Additionally, the model maintains sheet thickness, preserving material strength during forming.